A Sociological Analysis of Religious Conversion in the Case of Deddy Corbuzier - Pauzian, Muhamad Hilmi; Saepuloh, Aep; Rahman, Mohammad Taufiq (Jurnal Iman dan Spiritualitas, 2024)
This research aims to explore Deddy Corbuzier's religious conversion using a sociological analysis of religion. This research is a type of qualitative research with data collection through a netnographic study where researchers observe the YouTube channels of BEEM ARYO and Deddy Corbuzier, which discuss Deddy Corbuzier's conversion. The approach used is the sociology of religion. The discussion of this research includes religious conversion and the process and factors of Deddy Corbuzier's religious conversion. This research concludes that Deddy Corbuzier's religious conversion process took quite a long time from starting with environmental conditions, a crisis occurring, playing an active role in a particular religion, meeting with religious figures, then interacting with each other and finally making a commitment to change religions, thus getting its consequences for Deddy Corbuzier. Factors that influence this are interpersonal relationship factors, routine habit factors and religious leader factors. This research recommends comparative research on individuals or groups who undertake religious conversion or analysis of other approaches.